Analisis Pembiayaan Sektor Publik oleh Pemerintah dalam Meningkatkan Pelayanan Sosial Publik di Indonesia: Pendekatan Kualitatif - Ardianti, Putri Fania; Ramadhani, Annisa Dela; Zein, Ahmad Wahyudi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to explore and analyze the strategic role of public sector financing by the government in improving the quality of public services in Indonesia. With a qualitative approach, this study targets an in-depth understanding through semi-structured interviews, literature studies, and relevant policy analysis. The main focus of this study is how public budget planning, allocation, and management can affect the effectiveness of public services, both in terms of administrative efficiency and public satisfaction as service recipients. The results of the study indicate that the influence of public sector financing on improving services is largely determined by the extent to which the principles of transparency, accountability, and public participation are applied in the budgeting cycle and its implementation. In addition, cross-sector coordination, government apparatus capabilities, and the existence of a strong monitoring system are also important determinants in ensuring the use of the budget on target. These findings provide theoretical and practical contributions to the development of fiscal policies that support inclusive, responsive, and sustainable public services. This study recommends the need for public financing governance reform that is more adaptive to community needs and increased institutional capacity in managing public funds.